The Dynamics of Immunological Indices in Patients with Posttraumatic Osteomyelitis and Trophic Disoders of the Shin Tissues - Dekhtiarenko, N.O.; Hrytsai, M.P.; Tsokalo, V.M. (TERRA ORTHOPAEDICA, 2020)
Summary. The article deals with the study of immune status of patients with osteomyelitis and trophic disorders of the shin tissues. Objective: to evaluate the immune status of patients with shin-bone osteomyelitis and distrophic processes, and to study dynamics of immunological indices after surgical interventions (clearing and reconstructive restoring surgeries). Materials and Methods. The immune status of 52 patients with posttraumatic osteomyelitis and trophic disorders of the shin tissues was studied. Clinical, immunological, and statistical research methods were used. Results. The study revealed changes in immune defence and in trophic processes in tissues (bones, skin, and muscles) of the damaged extremity. Thus, the presence of changes in the immune status was established: a decrease in the number of T-lymphocytes, T-helpers, cytotoxic T-lymphocytes, as well as changes in the humoral immune system – a decrease in immunoglobulins M and G levels and an increace in the level of circulating immune complexes. Conclusions. Changes in systemic immunity and local trophic disorders revealed in patients mutually aggravate the course of the pathological process and complicate its elimination.